Changes in library and information science specialist training in response to current challenges - Shkitska, Iryna (Інформація та соціум, 2025)
The abstract highlights the need to review educational and professional programmes for training library specialists. This necessity arises from the evolving role of libraries in contemporary society and the expanding range of services they provide. The author proposes integrating new educational components into the curricula for future library, information, and archival specialists. These additions will enable future library professionals to optimise the performance of both traditional and novel professional tasks, interact more harmoniously with visitors, foster their comprehensive development, engage in grant activities, and effectively promote library institutions.